2020
DOI: 10.21203/rs.3.rs-31822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the immediate effect of COVID-19 lockdown on air quality: A case study of Delhi, India

Abstract: In India, the nationwide lockdown due to COVID-19 has been implemented on 25 March 2020. The lockdown restrictions on more than 1.3 billion people have brought exceptional changes in the air quality all over the country. This study aims to analyze the levels of three major pollutants (PM2.5, PM10, and NO2) before and during the lockdown in Delhi, one of the world’s most polluted cities. The data for PM2.5, PM10, and NO2 concentrations are derived from 38 ground stations dispersed within the city. The spatial i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Many countries face globally tremendous issues to mitigate the global pandemic COVID-19, and still, many countries are facing the same (Sikarwar and Rani 2020;Li et al 2020). The new infectious (COVID-19) disease was first identified in Wuhan City of China in December 2019 (Gautam et al 2021b;He et al 2020;Srivastava et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many countries face globally tremendous issues to mitigate the global pandemic COVID-19, and still, many countries are facing the same (Sikarwar and Rani 2020;Li et al 2020). The new infectious (COVID-19) disease was first identified in Wuhan City of China in December 2019 (Gautam et al 2021b;He et al 2020;Srivastava et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite several issues reported due to pandemic such as economy and human health, it was vice versa for pollution related issues. In 2020 several research studies showed a reduction in pollution levels in Delhi, which reflected improved air quality (Karuppasamy et al 2020;Agarwal et al 2020;Sikarwar and Rani 2020;Mahato et al 2020;Hamaa et al 2020;Srivastava et al 2020;Kumar et al 2020). All types of transportation services, including rail, road, air, and all industrial units except essential services, were suspended in 2020, leading to a dramatic reduction in air pollution (Kumari and Tosniwal 2020), but in 2021 there were exceptions given for movement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies by various scholars have shown how the lockdown has improved the ambient air quality, like in India (Gautam 2020;Mahato et al 2020;Sikarwar and Rani 2020;Srivastava et al 2020), U.S. (Berman and Ebisu 2020), Mexico (Méndez-Arriaga 2020), Kazakhstan (Kerimray et al 2020), Iran (Abdul Halim et al 2018),China (Fan et al 2020; Zambrano-monserrate et al 2020) especially in Wuhan (Cole et al 2020;Lu et al 2020;Sicard et al 2020;Song et al 2016; Q. Wang and Su 2020), Barcelona in Spain (Tobías et al 2020), Sao-Paulo in Brazil (Nakada and Urban 2020), Milan in Italy (Collivignarelli et al 2020), and Salé City in Morocco (Otmani et al 2020) In India, air pollution has become a topic of intense debate at all levels mainly because of the enhanced anthropogenic activities e.g. rapid urbanization, higher population growth, increased energy consumption, and vehicular emission and industrial emission (Dadhich et al 2018;Ghose et al 2005;Gupta et al 2008).…”
Section: Introductionmentioning
confidence: 99%